2010
DOI: 10.1007/s12524-010-0038-2
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial modeling of Brown oak (Quercus semecarpifolia) habitats in the Kumaun Himalaya under climate change scenario

Abstract: The study explores the use of multiple criteria decision techniques in predicting spatial niche of Brown oak (also known as Kharsu oak, Quercus semecarpifolia Sm.) formation in midaltitude (2,400-3,500 meter amsl) Kumaun Himalaya. Predictive models using various climatic and topographical factors influencing Brown oak's growth and survival were developed to define its current ecological niche. Analytical Hierarchical Process (AHP) method involving Saaty's pair-wise comparison was performed to rank the explanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 29 publications
(15 reference statements)
0
14
0
Order By: Relevance
“…The study is consistent with most of the previous reports, suggesting failure of Brown Oak regeneration in the Himalaya region (Tewari et al, 2019), but it provides additional information on the status of seedlings and likely regeneration potential of Brown Oak across a much broader altitudinal range (2,500 to 3,200 m) up to the timberline; particularly in the District of Chamoli, where there is evidence of declining patterns of precipitation. An earlier study by Saran et al (2010) concluded that there can be a reduction of 40% or as much as 76% in the stands of Q. semecarpifolia in present habitats; if there is a 1 or 2°C global temperature rise, respectively, as predicted (IPCC, 2014). Evidence also indicates a relatively higher rate of temperature rise in some regions of the Himalayas (1.5°C) in recent decades compared to the global average (Shrestha et al, 2012), suggesting that the pressure on survival of Q. semecarpifolia may be even more severe than predicted by some conservative estimates.…”
Section: Resultsmentioning
confidence: 92%
“…The study is consistent with most of the previous reports, suggesting failure of Brown Oak regeneration in the Himalaya region (Tewari et al, 2019), but it provides additional information on the status of seedlings and likely regeneration potential of Brown Oak across a much broader altitudinal range (2,500 to 3,200 m) up to the timberline; particularly in the District of Chamoli, where there is evidence of declining patterns of precipitation. An earlier study by Saran et al (2010) concluded that there can be a reduction of 40% or as much as 76% in the stands of Q. semecarpifolia in present habitats; if there is a 1 or 2°C global temperature rise, respectively, as predicted (IPCC, 2014). Evidence also indicates a relatively higher rate of temperature rise in some regions of the Himalayas (1.5°C) in recent decades compared to the global average (Shrestha et al, 2012), suggesting that the pressure on survival of Q. semecarpifolia may be even more severe than predicted by some conservative estimates.…”
Section: Resultsmentioning
confidence: 92%
“…Brown oak (Quercus semecarpifolia Sm.) is a major forestforming species at higher mountain elevation (2,400-3,500 m asl) in the Himalayas (Singh et al 1997;Saran et al 2010). Because of their remote distribution and less human influence coupled with biological and structural complexity and unique ecosystem functions, they are often regarded as old-growth forests by researchers in the Himalayas (Tashi 2004;Dorji et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…SDMs have long been used to support the management of invasive species (e.g. Anderson et al 2003, Kumar and Stohlgren 2009, Adhikari et al 2012, or to predict the spatial dispersal of invasive species under projected climate change (Anderson et al 2003, Thomas et al 2004, Thuiller et al 2009, Saran et al 2010. While a large number of statistical and machine-learning models are used in SDM (Hao et al 2019), the approach used in recent years has often been to combine/average the projections obtained from different individual methods into socalled ensemble projections (Araújo and New 2007).…”
Section: Habitat Suitability Projections Under Current and Future Cli...mentioning
confidence: 99%